Efecto de la posición inicial sobre la respuesta de reacción en las acciones de ataque en esgrima - Gutiérrez-Dávila, M.; Giles-Girela, F. J.; Zinseng, C.; Gutiérrez-Cruz, C.; Rojas, F. J. (Revista Internacional de Ciencias del Deporte, 2013)
The main aim of this study was to determine the effect that produced the displacement of the weight of the body towards the back foot, in the position of "en garde", with regard to an equidistant distribution of both supports and the habitual position, on the speed of horizontal displacement of the center of mass, CM, during a lunge attack in fencing. 19 fencers (14 men and 5 women), with an experience in regional competition of more than five years participated in this study. Two force platforms, operating to 500 Hz, a video camera, to 210 Hz and an electronic chronometer adapted to the system of wired up of the sword were used to record data. An electronic signal was used to synchronise all the recording systems mentioned. For the experimental situation where the CM was moving towards the back foot (backward), the fencer adopted the position of "en garde" with a vertical force on the back foot, between 65 % and 75 % of the corporal weight, and between 45 % and 55 % for the experimental situation of equidistant (equidistant) distribution of both supports. In a third situation, the fencer adopted his/her habitual position of "en garde". The results indicated that, the backward position increases the time of movement and the speed of the CM decreases during the movement initiation of the lunge attack.